Surface integrity and residual stress analysis of μEDM coated Ti-alloy miniature components. Issue 1 (2nd January 2021) - Mohanty, Shalini; Das, Alok Kumar; Dixit, Amit Rai
ABSTRACT: This work contributes to the surface topographical study of miniature Ti-alloy coated samples prepared by the micro-electrical discharge coating process using powder mixed dielectric medium. Two phases of experiments were conducted, first phase: using tungsten disulfide mixed in de-ionized water and second phase: using molybdenum disulfide powders mixed in deionized water. The produced micro-parts from both the phases of experiments were characterized for micro-hardness, indentation depths, wettability (in terms of the surface contact angle), residual stress, surface roughness, and surface crack density. The results indicated that MoS2 coating is superior as compared to WS2 coating obtained through the micro-EDM process for tribological applications where lubrication is necessary. The WS2 coated samples have micro-hardness ranging from 705.8 HV to 880.34 HV, surface roughness from 0.604 microns to 0.660 microns, and a comparatively higher surface crack density and residual stresses are developed on the recast surface than the samples coated with MoS2 powders. The samples coated with MoS2 powders have a micro-hardness variation from 658.21 HV to 714.21 HV, surface roughness between 0.561 μm to 0.650 μm.